Sport facility operations management : a global perspective - Schwarz, Eric C.; Hall, Stacey A.; Shibli, Simon (New York : Routledge, 2015)
Prologue 1. Introduction to Sport Facility Operations Management Part 1: Pre-Management and Pre-Operations Issues 2. Ownership Structures 3. Financing Sport Facilities 4. Capital Investment Appraisal 5. Planning, Design, and Construction Processes Part 2: Implementation of Management and Operations 6. Organizational Management 7. Human Resource Management 8. Financial Management 9. Operational Decision Making 10. Operations Management 11. Legal Concerns for Owners and Managers Part 3: Ancillary Issues in Operations Management 12. Marketing for Sport Facility Operations Management 13. Event Planning in Sport Facility Operations Management 14. Risk Assessment in Sport Facility Operations Management 15. Security Planning for Sport Facility Operations Management Part 4: Effectiveness of Management and Operations 16. Benchmarking and Performance Management for Sport Facilities.
Includes bibliographical references and index.
Keywords: Sports facilities -- Management; Sports administration